2021
DOI: 10.1038/s41379-020-00658-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, morphologic, and genomic findings in ROS1 fusion Spitz neoplasms

Abstract: The presence of a characteristic chimeric fusion as the initiating genomic event is one defining feature of Spitz neoplasms. Characterization of specific subtypes of Spitz neoplasms allows for better recognition facilitating diagnosis. Data on clinical outcomes of the specific tumor types may help in predicting behavior. In this study we present the largest series to date on ROS1 fusion Spitz neoplasms. We present the clinical, morphologic and genomic features of 17 cases. We compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 33 publications
6
45
0
Order By: Relevance
“…Nonetheless, large cells were described in 9 of 11 ROS1 fused Spitz neoplasms in a study by Wiesner et al (2), and up to 8 mitoses per square millimeter were reported in a study of such proliferations by Donati et al (65) Immunohistochemistry for ROS1 protein is a reliable surrogate for molecular testing (Figure 3c). Studies have confirmed that the vast majority (97.4%) of Spitz melanocytic proliferations harboring ROS1 fusions display ROS1 cytoplasmic positivity on immunohistochemistry (2,32). It is important to note, though, that immunohistochemical staining is often weak yet diffuse.…”
Section: Ros1 Fusionsmentioning
confidence: 95%
See 4 more Smart Citations
“…Nonetheless, large cells were described in 9 of 11 ROS1 fused Spitz neoplasms in a study by Wiesner et al (2), and up to 8 mitoses per square millimeter were reported in a study of such proliferations by Donati et al (65) Immunohistochemistry for ROS1 protein is a reliable surrogate for molecular testing (Figure 3c). Studies have confirmed that the vast majority (97.4%) of Spitz melanocytic proliferations harboring ROS1 fusions display ROS1 cytoplasmic positivity on immunohistochemistry (2,32). It is important to note, though, that immunohistochemical staining is often weak yet diffuse.…”
Section: Ros1 Fusionsmentioning
confidence: 95%
“…In addition to solitary lesions with typical desmoplastic Spitz nevus morphology, other melanocytic proliferations with HRAS mutations and/or 11p gain have also been described, including agminated Spitz nevi with or without associated nevus spilus (25)(26)(27)(28), recurrent Spitz nevi (30), melanocytic nevi with deep penetrating nevus-like morphology (21), pseudogranulomatous Spitz nevi (31) and a combination of syringocystadenoma papilliferum, tubular adenoma and a Spitz nevus (24). Moreover, the desmoplastic Spitz nevus phenotype is not restricted to HRAS mutated lesions since rare Spitz nevi harboring ROS1, ALK or even a BRAF fusion exhibiting a desmoplastic Spitz nevus morphology have been described (2,32).…”
Section: P Amplified And/or Hras Mutated Spitz Melanocytic Proliferationsmentioning
confidence: 99%
See 3 more Smart Citations